Automatic Exchange of Information Sebagai Big Data di Bidang Perpajakan - Selvi Selvi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
Economic globalization between countries becomes commonplace. Differences in financial rules are used for many parties to practice the Basic Erosion and Shifting Profit (BEPS) which leads to state losses. In tackling it has been agreed to implement Automatic Exchange of Information (AEoI), which automatically converts data into large data in the field of taxation.The research method of this paper is a literature study which combines several related literature and global and national implications using secondary data.Drawing up the conclusion that AEoI challenges have been theoretically overcome by Indonesia as a developing country. However, practically mash has not been able to find out whether it can be overcome or not because Indonesia still has not implemented AEoI